HIP1R acts as a tumor suppressor in gastric cancer by promoting cancer cell apoptosis and inhibiting migration and invasion through modulating Akt. Issue 9 (16th June 2020) - Zhu, Jinliang; Wang, Xin; Guan, Huiyuan; Xiao, Qiong; Wu, Zhonghua; Shi, Jinxin; Zhang, Fei; Gao, Peng; Song, Yongxi; Wang, Zhenning
Abstract: Background: Huntingtin‐interacting protein 1‐related (HIP1R) is a multi‐domain gene that exerts many cellular functions including altering T cell–mediated cytotoxicity and controlling intracellular trafficking. However, its clinical significance and function in gastric cancer (GC) have not been described. Methods: The expression levels of HIP1R were tested by the transcriptional and translational expression analysis and immunohistochemistry (IHC) in matched adjacent non‐tumorous vs tumor tissue specimens. The biological function of HIP1R on apoptosis, migration, and proliferation was evaluated by flow cytometry, Transwell, Cell Counting Kit‐8 (CCK‐8) assays, colony formation assays, and EdU labeling assays, respectively. Results: We found downregulated HIP1R in GC compared with adjacent non‐tumorous tissue, and HIP1R expression associated with N classification. We further found that the expression of HIP1R could induce apoptosis and inhibit proliferation, migration, invasion of GC cells, possibly through modulating Akt. Conclusions: Our data indicate that HIP1R may act as a potential diagnostic biomarker and a tumor suppressor gene in GC, potentially representing a novel therapeutic target for future GC treatment.